Research and solutions on normative constraints to gender equality and climate resilience - Shoby Michael; Milan Shobi (CGIAR GENDER Impact Platform, 2023)
Steve Cole, lead of the HER+ TRANSFORM work package, emphasizes that discriminatory social institutions serve as key drivers of numerous challenges in Tanzania and Nigeria. He sheds light on an innovative framework designed to investigate normative constraints to gender equality in agrifood systems. The fireside conversation with Dr Padmaja Ravula, senior scientist at ICRISAT India, affirms the relevance of addressing gender norms in the context of climate change, particularly in South Asia.